Diagnosis of pulmonary artery sarcoma with esophageal endoscopic ultrasound-guided needle aspiration - de Grauw, Arianna Johanna; Ravaglia, Claudia; Sultani, Fabio; Martinello, Sabrina; Dubini, Alessandra; Barbieri, Simone; Piciucchi, Sara; Stella, Franco; Poletti, Venerino (Rassegna di Patologia dell'Apparato Respiratorio, 2023)
Intraluminal sarcoma of the pulmonary artery is a rare malignant neoplasm with aggressive behaviour. Differential diagnosis with pulmonary embolism, metastasis or even pseudotumors can be complex and the site of the tumour can pose a significant diagnostic challenge, as the pulmonary arteries are not easily accessible for diagnostic sampling. We describe a case of primary pulmonary artery sarcoma diagnosed with endoscopic ultrasound-guided needle aspiration/biopsy through transesophageal access.